Perbedaan Tingkat Caregiver Burden Yang Merawat Lansia Demensia Di Panti Wreda - Heru Ginanjar Triyono; Meidiana Dwidiyanti; Rita Hadi Widyastuti (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2018)
Background: The prediction of the number of elderly people in Indonesia will increase along with changes in Indonesia's demographic status. Elderly people who feel that at home less socialize with elderly people choose to live in a nursing home, this is an alternative for the elderly, elderly degenerative diseases are very diverse one of which is elderly dementia with dementia will require a level of dependence beyond the elderly who do not have dementia. Caregivers who treat the elderly with dementia will be very vulnerable to burden in treating elderly dementia.Purpose: The purpose of this study was to analyze the difference in the level of caregiver burden who care for elderly dementia at a nursing home.Method: This research method uses